Simulation study of the effect of the chemical heterogeneity of activated carbon on water adsorption - Miguel Jorge (2002)
In this paper we present results from the molecular simulation of water adsorption in slit-shaped activated carbon pores. We calculate adsorption isotherms by grand canonical Monte Carlo (GCMC) simulation, Henry's constants by Monte Carlo integration, and vapor-liquid equilibrium data by the gauge-cell Monte Carlo method, to investigate the chemical heterogeneity of activated carbon adsorbents. Several types of polar oxygen-containing sites are placed on the surface of the carbon with different densities and local distributions, in order to determine the individual effects of each of these factors on the adsorption of water. Our results confirm the role of surface sites in the enhancement of water adsorption, Furthermore, we show that the local distribution of these sites has a strong effect on low-pressure adsorption, while the overall site density affects mainly the vapor-liquid phase transition. The type of oxygen-containing group is shown not to be of critical importance, since more complex groups can effectively be represented by simpler sites. This study forms the basis for the development of a model for activated carbon that is able to represent the chemical heterogeneity of this type of material.